2008
DOI: 10.1039/b806995f
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous peptides as experimental models for hydration water dynamics near protein surfaces

Abstract: We report quasi-elastic neutron scattering experiments to contrast the water dynamics as a function of temperature for hydrophilic and amphiphilic peptides under the same level of confinement, as models for understanding hydration dynamics near chemically heterogeneous protein surfaces. We find that the hydrophilic peptide shows only a single non-Arrhenius translational process with no evidence of spatial heterogeneity unlike the amphiphilic peptide solution that exhibits two translational relaxations with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 55 publications
3
58
0
Order By: Relevance
“…Earlier studies of hydrogen bond lifetimes between water molecules and the protein HP-36 have revealed a significantly heterogeneous distribution of hydrogen bond lifetimes, exhibited around different helices of the protein (33,34). Experimental proof for this fact has been provided before by quasielastic neutron scattering, which showed a heterogeneous dynamic signature for amphiphilic peptides (35). For proteins, the work by Zhang et al (36) was able to map the heterogeneous distribution of the coupled solvation-protein fluctuations at tryptophan probes using coherent femtosecond laser preparation.…”
Section: Resultsmentioning
confidence: 81%
“…Earlier studies of hydrogen bond lifetimes between water molecules and the protein HP-36 have revealed a significantly heterogeneous distribution of hydrogen bond lifetimes, exhibited around different helices of the protein (33,34). Experimental proof for this fact has been provided before by quasielastic neutron scattering, which showed a heterogeneous dynamic signature for amphiphilic peptides (35). For proteins, the work by Zhang et al (36) was able to map the heterogeneous distribution of the coupled solvation-protein fluctuations at tryptophan probes using coherent femtosecond laser preparation.…”
Section: Resultsmentioning
confidence: 81%
“…We have completed molecular dynamics simulations using non-polarizable and polarizable protein force fields to contrast the water dynamics near hydrophilic, N-acetyl-glycine-methylamide (NAGMA), and amphiphilic, N -acetyl-leucine-methylamide (NALMA) peptides as a function of temperature, as models for understanding temperature dependent hydration dynamics near chemically heterogeneous protein surfaces7276. These simulations are tightly coupled to X-ray diffraction and quasi-elastic neutron scattering (QENS) perfomed on these same systems at the same concentrations.…”
Section: Condensed Phase Structure and Dynamicsmentioning
confidence: 99%
“…Given the qualitative improvement in solution structure using the AMOEBA model, we also compared the changes in water dynamics as a function of temperature against our experimental data. Based on quasi-elastic neutron scattering (QENS) experiments, the amphiphilic NALMA peptide solution exhibits two translational relaxations at low temperatures, while the hydrophilic peptide shows only a single translational process, with transport properties of water near both peptide chemistries being very suppressed with respect to bulk dynamics 75,76. This is a real stress test for any force field given the range of dynamical trends that depend on amino acid chemistry and temperature.…”
Section: Condensed Phase Structure and Dynamicsmentioning
confidence: 99%
“…Interfacial water plays a very important role in the structure and the dynamics of proteins as it shapes the potential energy landscape that governs their folding, structure, stability, and function. [7][8][9] Protein dynamics seems to be slaved to the dynamics of water fluctuations. [10] On the other hand, protein activity is also related to its dynamics, so that gaining insight into the properties of interfacial water becomes crucial to understand the microscopic mechanisms of protein function.…”
Section: Introductionmentioning
confidence: 99%
“…[10] On the other hand, protein activity is also related to its dynamics, so that gaining insight into the properties of interfacial water becomes crucial to understand the microscopic mechanisms of protein function. [9,11] A large variety of techniques have been used to address the question of the structure and dynamics of interfacial water, also called hydration water, [7] over several time scales, from Xray crystallography to dielectric spectroscopy (microseconds to 0.1 ns), [12,13] magnetic relaxation dispersion spectroscopy and terahertz spectroscopy (picoseconds), [7,14,15] inelastic neutron scattering (0.1-100 ps), [16] or fluorescence and photon-echo…”
Section: Introductionmentioning
confidence: 99%